A simple unlabeled human chorionic gonadotropin biosensor based on a peptide aptamer. Issue 38 (7th September 2021) - Li, Huanhuan; Cai, Tongji; Ren, Yi; Huang, Jing; Jiang, Hanbing; Hou, Yucui; Tang, Chunhua; Yang, Jie; Zhao, Jia; Yu, Peng
Abstract : As an essential biochemical indicator in the fields of pregnancy and oncology, HCG can be evaluated using colloidal gold immunochromatographic paper and quantified using a biochemical analyzer based on the principle of the antibody sandwich method. Abstract : As an essential biochemical indicator in the fields of pregnancy and oncology, human chorionic gonadotropin (HCG) can be evaluated using colloidal gold immunochromatographic paper and quantified using a biochemical analyzer based on the principle of the antibody sandwich method. In view of the inaccuracy of the former and the complication of the latter, this study constructed an accurate, sensitive and simple unlabeled biosensor based on peptide aptamer CGGGPPLRINRHILTR for HCG detection. Molecular Operating Environment (MOE) was used to simulate the aptamer and protein docking, and western blot (WB) was used to verify the binding effect and ratio. The peptide aptamer was characterized and was then reduced with tris-(2-carboxyethyl)-phosphine hydrochloride (TCEP). After electrochemical deposition of chloroauric acid on the screen-printed electrode (SPE), the aptamer was self-assembled on the electrode surface under optimal conditions. The active site of the electrode surface was blocked with 6-mercapto-1-hexanol (MCH) and BSA. The electrochemical impedance spectrum (EIS) was used to quantify HCG in the matrix. Showing a good linear relationship in the range of 5–1500 mIU mL −1, with a detection limit of 1 mIU mL −1, the biosensor remained stable at room temperature for 14 days. Because of its small size, stability, sensitivity and accuracy, this biosensor has great potential to become a portable diagnostic device for HCG.